2014
DOI: 10.1109/tia.2013.2267710
|View full text |Cite
|
Sign up to set email alerts
|

Time Synchronization of Automation Controllers for Power Applications

Abstract: This paper investigates various forms of industrial time synchronization and attempts to apply them to Programmable Automation Controllers (PACs) for power system applications. PACs have been used in industry for many control applications, but advancements in synchronization technology has allowed for PACs to be used in high speed control and data acquisition systems. This paper looks at utilizing a PAC as a time synchronized Sequence of Events recorder (SER) for substation automation. It is shown that a PAC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The synchronous reference clock is needed to ensure that the operation probabilities with the same time stamp are used in the further analysis. The synchronization system based on Global Positioning System widely applied in substations could provide the desired unified clock …”
Section: Proposed Identification Methods Of Protection Misoperationmentioning
confidence: 99%
“…The synchronous reference clock is needed to ensure that the operation probabilities with the same time stamp are used in the further analysis. The synchronization system based on Global Positioning System widely applied in substations could provide the desired unified clock …”
Section: Proposed Identification Methods Of Protection Misoperationmentioning
confidence: 99%
“…This way the basic LTE Advanced system is not changed and standard hardware might be deployed. Utilization of a GPS-based clock synchronization method [11] is proposed to solve the problem of synchrony of the communication. By having a synchronized clock in every wireless connected device, the execution of actions can be based on this common timestamp instead of the varying arrival of a message.…”
Section: Proposed Wireless Communication Systemmentioning
confidence: 99%
“…Previous work has shown that automation controllers can be synchronized to the same timescale and accuracy of the electrical protection network [17].…”
Section: Industrial and Commercial Power Systems Justificationmentioning
confidence: 99%